2022
DOI: 10.1021/acssuschemeng.2c00873
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Ruthenium(II)-Catalyzed C–H Activations in and on H2O

Abstract: Catalyzed C−H activation has surfaced as an enabling tool for molecular assembly, with a plethora of translational applications. The enormous developments toward the utilization of ubiquitous C−H bonds as latent functionalities has thus enabled the efficient assembly of increasingly complex scaffolds. Recently, a paradigm shift has occurred to enable sustainable, industry-relevant C−H functionalization manifolds. Among the most prominent transition metals for C−H activations, ruthenium offers several salient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 129 publications
0
16
0
1
Order By: Relevance
“…The electrophilic chloro-group at the para-position of phenyl 1 h also proved to be feasible (10), without any ortho-arylation observed. [20] The meta-CÀ H glycosylation was not restricted to pyridine-guided functionalization. Indeed, a plethora of heterocycles, such as pyrazole 1 i, purine derivatives 1 j-1 l and quinoline 1 m, was identified as amenable substrates for the challenging meta-C-aryl glycosides assembly (11)(12)(13)(14)(15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrophilic chloro-group at the para-position of phenyl 1 h also proved to be feasible (10), without any ortho-arylation observed. [20] The meta-CÀ H glycosylation was not restricted to pyridine-guided functionalization. Indeed, a plethora of heterocycles, such as pyrazole 1 i, purine derivatives 1 j-1 l and quinoline 1 m, was identified as amenable substrates for the challenging meta-C-aryl glycosides assembly (11)(12)(13)(14)(15).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the ruthenium-catalyzed meta-CÀ H glycosylation strategy was probed with different glycosyl bromides 2 (Scheme 3). Rhamnosyl bromide 2 b proved efficient to site-and stereo-selectively stitch rhamnose moiety into the meta-position of a series of heteroarenes (18)(19)(20). Diversely protected mannosyl bromides 2 c-2 e, containing acetyl and pivaloyl group, generated 21-26 with exclusive αanomeric selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Die elektrophile Chlorgruppe an der para-Position des Phenyls 1 h erwies sich ebenfalls als praktikabel (10), ohne dass eine ortho-Arylierung beobachtet wurde. [20] Die meta-CÀ H-Glykosylierung war nicht auf die Pyridin-gesteuerte Funktionalisierung beschränkt. Tatsächlich wurde eine Vielzahl von Heterozyklen, wie Pyrazol 1 i, Purinderivate 1 j-1 l und Chinolin 1 m, als geeignete Substrate für den anspruchsvollen Aufbau von meta-C-Arylglykosiden identifiziert (11)(12)(13)(14)(15).…”
Section: Ergebnisse Und Diskussionunclassified
“…24 Particular attention has been focussed on reactions in 2-methyltetrahydrofuran, [25][26][27][28] PEG-400, 29,30 diethyl carbonate, 31 deep-eutectic solvents, 32 and water. 33,34 In 2018, our group reported a direct C-H arylation procedure that was able to proceed at ambient temperature. [35][36][37] These studies revealed that the p-cymene ligand commonly Scheme 1 (A).…”
Section: Introductionmentioning
confidence: 99%
“…24 Particular attention has been focussed on reactions in 2-methyltetrahydrofuran, 25–28 PEG-400, 29,30 diethyl carbonate, 31 deep-eutectic solvents, 32 and water. 33,34…”
Section: Introductionmentioning
confidence: 99%